البرنامج العالمي للتثقيف في مجال حقوق الإنسان: خطة العمل، المرحلة الثانية - United Nations for Human Rights Office of the High Commissioner (United Nations, 2012)
The Plan of Action provides methodological guidance to develop a comprehensive human rights education strategy for young people at the national level that supports youth empowerment, participation and inclusion. It addresses governments, national human rights institutions and civil society organizations, including youth movements and networks, as well as education practitioners. Member States adopted the Plan of Action to guide implementation of the second phase (2010-2014) of the World Programme for Human Rights Education (2005-ongoing), proclaimed by the General Assembly in 2004 and structured in consecutive phases, each focusing on a specific target sector or thematic area.